Associations Between Relative Deprivation and Life Satisfaction During the COVID-19 Lockdown: Results of Serial Mediation Analyses - Chen, Junbo; Cao, Jun; Fu, Shuying; Jia, Xuji (Frontiers in Psychology, 2022)
With the COVID-19 pandemic, life satisfaction among college students has become a key issue at universities and in society. The current study explores the effects of belief in a just world and resilience on the relationship between relative deprivation and life satisfaction. A total of 787 college students from universities in China completed online questionnaires. Results showed that relative deprivation was negatively correlated with life satisfaction. Belief in a just world and resilience separately mediated the relationship between relative deprivation and life satisfaction. Moreover, a serial mediating effect of belief in a just world and resilience was observed between relative deprivation and life satisfaction. These findings suggest that relative deprivation may impair individuals' beliefs in a just world. Moreover, less belief in a just world may lower resilience and consequently decrease life satisfaction. This study enriches the research field of relative deprivation theory in the context of the COVID-19 pandemic, and provides a new interpretation and intervention perspective for improving college students' life satisfaction.